An accurate method for the calculation of ultimate load in lattice boom - Liming Zhou; Jinghao Tang; Weijie Wang; Erfei Zhao; Shuhui Ren; Qixun Zhang; Peng Liu (Advances in Mechanical Engineering, 2019)
To calculate the ultimate load of the lattice boom accurately, the effective length factor and imperfection factor are introduced to the current stability factor formula. First, we propose a stability factor formula by conducting a series of tests of high-strength steel tubes under axial compression and analyzing the experimental data. Second, the effective length factor of the chord which is caused by braces is calculated on the basis of different effective length factors and stability curves. Then, the correctness of the proposed effective length factor and the stability factor formula are proved by destructive tests under three loading modes. Using the modified stability factor formula, the accuracy of ultimate load of lattice boom is enhanced. These findings will be of great value for improving the design level of lattice boom and providing a theory and test basis for the completion of the buckling design method of the high-strength steel tubes.